Beating the bubble: Using kinematic triggering in the bubble lens for acquiring small, dense targets - Mott, Martez; Wobbrock, Jacob O. (ACM Conference on Human Factors in Computing Systems (CHI), 2014)
We present the Bubble Lens, a new target acquisition technique that remedies the limitations of the Bubble Cursor to increase the speed and accuracy of acquiring small, dense targets–precisely those targets for which the Bubble Cursor degenerates to a point cursor. When targets are large and sparse, the Bubble Lens behaves like the Bubble Cursor. But when targets are small and dense, the Bubble Lens automatically magnifies nearby targets, making them larger in both visual- and motor-space. Importantly, magnification is not governed by an explicit user-invoked mode-switch. Rather, magnification is activated through kinematic triggering, a technique that continuously examines an unfolding velocity profile to automatically trigger mode changes based on observed features. In a first study, we found the Bubble Cursor performed poorly when targets had an effective size smaller than 10 pixels. Using this threshold for the Bubble Lens in a second study, we found that the Bubble Lens significantly outperformed the Bubble Cursor, decreasing movement time by 10.2% and error rates by 37.9%, making the Bubble Lens the fastest current pointing technique.